Fiscal Accounting Strategies in Optimizing Local Revenue Through Taxes on PKB and BBNKB - Subki, Fadhila Humaira; Martiningsih, Rr. Sri Pancawati (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to examine how fiscal accounting techniques are used in NTB Province to handle PKB and BBKNB. This type of study involves a case study that uses descriptive techniques. Documentation and in-depth interviews with the Head of the Technical Implementation Unit (UPTB) of the Regional Tax Service Unit (UPPD) of Mataram City were used to collect data.  The results of the study showed that the following strategies were used to enhance PKB and BBNKB revenue: 1) Community socialization, 2) Increasing the level of assistance provided to taxpayers 3) Law enforcement by working with Jasa Raharja and other law enforcement partners, 4) Offering tax benefits and lottery prizes as a way of showing encouragement.